Dietary risk factors of non-communicable diseases among industrial common workers: a cross-sectional study - Upadhyay, Dakshadhwari; Ahmed, Rashmi; Boruah, Manjit (International Journal Of Community Medicine And Public Health, 2019)
Background: Non-communicable diseases (NCDs) are the leading cause of death and morbidity throughout the world. Unhealthy diet is a risk factor for NCDs. There is a lack of studies on the prevalence of dietary risk factors among the industrial population in India particularly in North East India. Methods: A cross-sectional study was conducted among industrial workers of a major industry in Assam. The sample size was 330 considering a prevalence of 50% and 95% confidence interval, and a design effect of 1.5. Data was collected using methods described in WHO STEPS instrument v3.1. Results: A total of 318 subjects consented to participate in the study. Consumption of less than 5 servings of fruit and/or vegetables on average per day was observed in majority 98.4% of the study participants. In a typical week, fruits and vegetables were consumed on 2.99 and 6.89 days respectively. Mean number of servings of fruit consumed on average per day was 0.5 and for vegetables were 2.33.46 (14.5%) of the study participants added extra salt always or often to their food before eating or while eating. 132 (41.5%) of the study participants always or often ate processed foods high in salt. Conclusions: Inadequate consumption of fruits and vegetables was observed in 98.4% of industrial workers included in the study. Increasing awareness among this population about adequate consumption of fruits and vegetables to prevent NCDs is necessary.